Acute Stress Decreases but Chronic Stress Increases Myocardial Sensitivity to Ischemic Injury in Rodents - Eisenmann, Eric D.; Rorabaugh, Boyd R.; Zoladz, Phillip R. (Frontiers in Psychiatry, 2016)
Cardiovascular disease is the largest cause of mortality worldwide, and stress is a significant contributor to the development of cardiovascular disease. The relationship between acute and chronic stress and cardiovascular disease is well-evidenced. Acute stress can lead to arrhythmias and ischemic injury. However, recent evidence in rodent models suggests that acute stress can decrease sensitivity to myocardial ischemia-reperfusion injury. Conversely, chronic stress is arrythmogenic and increases sensitivity to myocardial ischemia-reperfusion injury. Few studies have examined the impact of validated animal models of stress-related psychological disorders on the ischemic heart. This review examines the work that has been completed using rat models to study the effects of stress on myocardial sensitivity to ischemic injury. Utilization of animal models of stress-related psychological disorders is critical in the prevention and treatment of cardiovascular disorders in patients experiencing stress-related psychiatric conditions.